Square footage requirement of weaned pigs - Koch, B.A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred and twenty weaned pigs were used to evaluate the effect of space allowance. Pigs were housed in a control environment nursery with woven wire flooring with 4, 6, 8, 10, or 12 head per 4' x 5' pen which allowed 4.5, 3.0, 2.25, 1.8, and 1.5 square feet of usable space, respectively, for each pig. No significant differences were observed in performance for the five-week period. However, during week 3,4, and 5 of the trial, pigs with 1.8 and 1.5 sq. ft. of space, respectively, had a markedly reduced feed intake and average daily gain. Feed gain ratios were not affected. This study suggests a minimum of 2.25 sq. ft. will support pig performance equal to those pigs allowed more space for the 5-week period.
Keywords: Swine; Weaned pigs; Housing